Better Use of Science for Better EU Regulation. (September 2014) - Schrefler, Lorna; Pelkmans, Jacques
Abstract : Risk regulation is a major task of the EU. In this context, scientific knowledge and advice is critical to the preparation, formulation, legislation and later revision of EU risk regulation. However and with some notable exceptions (e.g. some EU Agencies, DG SANCO), there seems to be no systematic view, let alone, organisation for the 'use of science' for EU policy–making. It is in this light that the new function of Chief Scientific Advisor (CSA) to the President of the European Commission can best be appreciated. The authors first sketch how 'science' is used in the EU regulatory regime and what is or has become problematic about it. Subsequently, an informal SWOT analysis of the 'use of science' for EU policy is conducted. The contribution ends with an attempt to evaluate the CSA's accomplishments to date and how it can contribute to improving EU regulation. This is followed by a few recommendations on how the role of the CSA could be strengthened in the near future.